Scalable and thermally-integrated solar water-splitting modules using Ag-doped Cu(In, Ga)Se2 and NiFe layered double hydroxide nanocatalysts. Issue 22 (19th May 2022) - Bayrak Pehlivan, İlknur; Saguì, Nicole A.; Oscarsson, Johan; Qiu, Zhen; Zwaygardt, Walter; Lee, Minoh; Mueller, Martin; Haas, Stefan; Stolt, Lars; Edoff, Marika; Edvinsson, Tomas
Abstract : A thermally-integrated solar water-splitting approach is presented, using bifunctional precious metal free catalysts based on Fe and Ni. The approach is scalable and reaches up to 13.4% solar-to-hydrogen (STH) efficiency. Abstract : Photovoltaic (PV) electrolysis is an important and powerful technology for environmentally-friendly fuel production based on solar energy. By directly coupling solar cell materials to electrochemical systems to perform water electrolysis, solar energy can be converted into hydrogen fuel utilizing locally-generated heat and avoid losses from DC–DC convertors and power grid transmission. Although there have been significant contributions to the photoelectrochemical and PV-electrolysis field using isolated laboratory cells, the capacity to upscale and retain high levels of efficiency in larger modules remains a critical issue for widespread use and application. In this study, we develop thermally-integrated, solar-driven water-splitting device modules using AgCu(In, Ga)Se2 (ACIGS) and an alkaline electrolyzer system with NiFe-layered double hydroxide (LDH) nanocatalysts with devices of 82–100 cm 2 area. The Ga-content in the ACIGS solar cells is tuned to achieve an optimal voltage for the catalyst system, and the average efficiencies and durability of the PV-electrolyzer were tested in up to seven-day indoor and 21 day outdoor operations. We achieved a solar-to-hydrogen (STH) module efficiency of 13.4% from gas volume measurements for the system with a six-cell CIGS-electrolyzer module with an active area of 82.3 cm 2 and a 17.27% PV module efficiency under 100 mW cm −2 illumination, and thus 77% electricity-to-hydrogen efficiency at one full sun. Outdoor tests under mid-Europeen winter conditions exhibited an STH efficiency between 10 and 11% after the initial activation at the installation site in Jülich, Germany, in December 2020, despite challenging outdoor-test weather conditions, including sub-zero temperatures.